Diagnosis of public management actions aimed at water supply and sanitation in the cities located in Lagoa Mirim and Canal São Gonçalo Watersheds - Branco Filho, Thelmo de Carvalho Teixeira; Silva , Elisa Inácio da; Bartz, Isadora (ANAP Brazil, 2021)
.